Cognitive Conflicts Emerged from Feedback from Peer Assessment and Artificial Intelligence - Khaira Rizqa; Nur Arifah Drajati; Kristian Adi Putra (Al-Hayat: Journal of Islamic Education, 2022)
This narrative study explores the cognitive conflicts that pre-service teachers experience during peer-assessment activities in an artificial intelligence (AI) facilitated academic writing course. This study applies a narrative inquiry research design to Indonesian English as a Foreign Language (EFL) writing classes. Three pre-service teachers pursuing an undergraduate degree in English language education at an Indonesian public university were recruited. The data were obtained from participants' stories, follow-up semi-structured interviews, and photos as an artifact to complete the data. The data was then analysed thematically. The participants’ cognitive conflict experiences were gathered during process writing and peer assessment. The findings show that the cognitive conflicts experienced by the participants were mostly from old myths and false beliefs. It brings advantages to pre-service teachers. The cognitive conflicts support the critical thinking of pre-service teachers. They discussed the material in detail, explored the different ideas, and helped them to confirm the incorrect knowledge and misunderstanding among them. This finding also implies the need for pre-service teachers, in-service teachers, and teacher educators to critically consider the cognitive conflicts in an L2 writing classroom, particularly in madrasah tsanawiyah (junior high schools), madrasah aliyah (senior high schools) and higher education institutions contexts.